Analysis of heart rate of powerlifting’s athletes in competitive situation - Mafra, Rafael (2011)
The objective of this study was to analyze the behavior of Heart Rate (HR) of powerlifting’s athletes in competitive situation and the possible modulation of the HR according to the sex of the athlete, type of exercise performed in the competition, competitive timing (approximation vs. performance) and initial or final attempt to lift the weight. Twenty healthy elite national volunteers athletes (nine men and eleven women), who were taking part at the 23rd Brazilian Powerlifting Championship in 2004 were monitored since the warming up until when the athlete left the competitive platform. The heart rate was monitored on the squat and dead lift exercises by the belt, sensor and the heart rate monitor frequency. The HR was registered only at the first and last attempt, and for the purpose of statistic registration of the dependent variable (HR), the lowest value reckoned in the interval of time between warming up and the execution of the movement and exit of the competitive platform was considered a HR of approximation (AHR) and the highest value was considered the peak of HR (HHR). In general our results show there is no significant difference in the behavior of HC between genders (p = 0.667), attempts (p = 0.567) and exercises (p = 0.741) only the competitive moment showed highly significant differences (p = 0000). It is concluded that there is no significant difference in the behavior of HR between genders, attempts and exercises and that the predominant factor in the modulation of HR is the intensity of muscle movement performed.